NONPARAMETRIC ESTIMATION OF DYNAMIC PANEL MODELS WITH FIXED EFFECTS. (27th May 2014) - Lee, Yoonseok
Abstract : This paper considers nonparametric estimation of autoregressive panel data models with fixed effects. A within-group type series estimator is developed and its convergence rate and asymptotic normality are derived. It is found that the series estimator is asymptotically biased and the bias could reduce the mean-square convergence rate compared with the cross-section cases. A bias corrected nonparametric estimator is developed.